2015
DOI: 10.1016/j.actamat.2015.06.016
|View full text |Cite|
|
Sign up to set email alerts
|

In situ TEM study of twin boundary migration in sub-micron Be fibers

Abstract: Deformation twinning in hexagonal crystals is often considered as a way to palliate the lack of independent slip systems. This mechanism might be either exacerbated or shut down in small-scale crystals whose mechanical behavior can significantly deviate from bulk materials. Here, we show that sub-micron beryllium fibers initially free of dislocation and tensile tested in-situ in a transmission electron microscope (TEM) deform by a {1012} 1011 twin thickening. The propagation speed of the twin boundary seems to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 71 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Zhang and Xiang (2018) developed a continuum model for shear coupling in low angle GBs in terms of the motion and reaction of the constituent dislocations that constitute the GB structure. Recent experiments and simulations demonstrated that the shear-coupling of highangle GBs (Rajabzadeh et al, 2013a,b;Mompiou et al, 2015) is associated with the motion of line defects known as disconnections (Bollmann, 1970;Ashby, 1972;Hirth and Pond, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Xiang (2018) developed a continuum model for shear coupling in low angle GBs in terms of the motion and reaction of the constituent dislocations that constitute the GB structure. Recent experiments and simulations demonstrated that the shear-coupling of highangle GBs (Rajabzadeh et al, 2013a,b;Mompiou et al, 2015) is associated with the motion of line defects known as disconnections (Bollmann, 1970;Ashby, 1972;Hirth and Pond, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed individual wires tested in SEM show a remarkable high yield stress around 2 GPa. 18 This fragile-like behavior is reinforced by the hci axis orientation of the wire that is unfavorable for the easy prismatic and basal dislocation glide. On the contrary, the twinned area can plastically deform by prismatic slip because its hci axis is almost perpendicular to the wire axis.…”
Section: Discussionmentioning
confidence: 99%
“…The wires were deformed by applying a uniaxial displacement on the sample glued on a copper grid. 18 In situ observations were performed on a JEOL2010 TEM (JEOL Ltd., Tokyo, Japan) operated at 200 kV. Video sequences were recorded on a hard drive/DVD writer using a MEGAVIEW III camera (Olympus Soft Imaging Solutions GmbH, Münster, Germany) at 22-25 fps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-tensile testing also encounters size effects in pure metals, such as copper [33], and requires understanding of both the obstacle spacing, microstructural constraints, and the dimensional constraints as discussed in Section 2. [42] and Cu [71], observations of twin boundaries in Be [73], and tensile strengths and modulus of Co nanowires conducted in situ SEM [72]. Depending on the length scale and initial sample structure, sample preparation time varied from large amounts for FIB-prepared samples in [42] to quick placement of nanowires in [72].…”
Section: Dolph Et Al Conducted Nanoindentation Tests On An Fe-9%cr mentioning
confidence: 99%